Empowering Primary School Teachers In Developing Contextual Sundanese Teaching Materials Based On Local Wisdom: A Community Engagement Program - Yudhie Suchyadi; Rini Sri Indriani; Resyi A Gani; Nita Karmila; Dilla Eka Aprilia; Haula Ramadhanie; Kamilah Nuraini (JURNAL MANAJEMEN PENDIDIKAN, 2026)
This community engagement study was conducted in response to the limited competence of primary school teachers in developing contextual and innovative Sundanese teaching materials. Although Sundanese language learning plays an important role in preserving local language, cultural identity, and regional wisdom, its implementation in primary schools is often constrained by textbook dependence, limited teacher creativity in material development, and insufficient integration of local cultural content into classroom learning. This study aimed to enhance primary school teachers’ competence in developing Sundanese teaching materials through community-based training and mentoring at SDN Kedung Badak 2, Bogor City. The study employed a descriptive qualitative design with a community engagement approach. The program was implemented through several stages, including preliminary observation, needs analysis, program socialization, training, workshop-based product development, mentoring, and evaluation. Data were collected through observation, interviews, documentation, product analysis, and participant evaluation, and were analyzed descriptively through data reduction, data display, interpretation, and conclusion drawing. The results indicate that the program improved teachers’ understanding and practical skills in designing Sundanese teaching materials that are more creative, contextual, and relevant to students’ learning needs. Teachers were able to develop learning modules, student worksheets, and simple instructional media integrating Sundanese local wisdom, such as folklore, proverbs, daily expressions, and cultural values. The mentoring process also strengthened teachers’ confidence in implementing the developed materials in classroom learning. In conclusion, community-based training and mentoring can serve as an effective and replicable model for improving teacher competence, strengthening local language learning, and supporting the preservation of Sundanese culture through primary education.